The Academy - Poyer, David (Dan Lenson novel, 2023)
"In his final tour of duty after a remarkable career at sea, Dan Lenson is appointed Superintendent of the US Naval Academy at Annapolis. He begins at a difficult time: Congress is cutting military budgets in the wake of the devastating world war with China, calls for radical reform are upending traditions, and Dan himself faces legal jeopardy for his actions during the war. And when a Category 5 hurricane threatens to overwhelm the coast, Dan must fight to rescue the Academy itself. Parallel to this narrative runs the dramatic story of Dan's years as a first class midshipman, 40 years ago. An Academy classmate commits suicide, and Dan is drawn into the investigation. The decisions he makes will affect his entire career and shape how he comes to lead troops in battle and at peace."--